DAMPAK WORK FROM HOME TERHADAP KINERJA GURU SD NEGERI 011 MEKAR SARI DUMAI SELATAN PADA MASA PANDEMI COVID 19 - Muhammad Heru Setiawan; Zariul Antosa; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Education is the responsibility of the whole community, especially the educational personnel provider institutions (LPTK). LPTK prepares educational transmitters by teaching things related to pedagogical abilities and the material to be taught. In learning activities, students are also trained to harmonize their pedagogical abilities with student characteristics and the availability of learning facilities and infrastructure. The rise of the covid outbreak at the beginning of 2020, made all people have to limit their activities outside the home. Due to the increasingly worrying covid outbreak, to break the chain of the virus's spread, the government asks all activities to be carried out from home (work from home), including in the field of education. The government's policy of changing face-to-face learning to WFH suddenly caused a culture shock for teachers and students. Through WFH, teachers are asked to simplify learning time and materials to be taught, change teaching methods or methods, change evaluation methods and so on. Furthermore, students must also change the way they learn, students must be able to find the substance of the material presented by the teacher independently, learn actively, complete the learning infrastructure, the role of parents must be increased in assisting students when learning independently. This change in the way of teaching with WFH not only makes teachers have to work hard to prepare lessons but also teachers have to provide extra time to serve students, or parents of students in understanding each material being taught. With limited learning facilities and infrastructure, WFH activities can only be carried out through online learning, which requires teachers to prepare tools (android) and a budget for purchasing data packages. The same is true for parents of students. Key Words: Impact of Work From Home on Teacher Performance, Covid 19 Pandemic Period